Analysis of Sensory, Preference, Physical and Chemical Characteristics of Cassava Pudding using Spherification Caviar Technique - Nikki Rahma Wijayanti; Octavianti Paramita (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This study investigated the effect of cassava puree incorporation on the sensory, physicochemical, and nutritional characteristics of pudding. An experimental design with two formulations was applied: F0 (control) and F1 (with cassava puree addition). Sensory evaluation was conducted by three trained panelists, while consumer acceptance testing involved 80 untrained panelists. Color attributes were analyzed using digital image processing, and chemical composition was determined through proximate analysis, including moisture, ash, fat, protein, carbohydrate, and crude fiber content. The sensory evaluation revealed no significant differences between F0 and F1 in terms of aroma, texture, and taste. Similarly, consumer acceptance results indicated no significant difference in overall preference between the two formulations (p = 0.470). Color analysis demonstrated that cassava puree addition did not significantly alter the visual appearance of the product. However, proximate analysis showed notable changes in chemical composition: moisture decreased by 1.70%, ash by 9.21%, fat by 8.21%, protein by 12.56%, and crude fiber by 65.62%, while carbohydrate content increased by 10.54%. These compositional changes suggest nutritional implications, particularly the enhancement of carbohydrate content as an energy source, despite reductions in several other nutrients. Overall, cassava puree incorporation did not significantly affect sensory acceptance or color attributes but altered the nutritional profile of the pudding. This study contributes to the scientific development of cassava-based food products through comprehensive evaluation of sensory, physical, and chemical properties, providing a foundation for alternative formulation strategies in starch-based desserts.